Investigation on the aging behaviour of the functionally gradient material consisting of boron carbide and an aluminum alloy - Sarikan, Bertan (Materiali in tehnologije, 2012)
In the current study the effect of different temperatures on the aging behaviour of a functionally gradient material was investigated to observe the variation of hardness with respect to the aging time. To do this, the functionally-gradient-material (FGM) specimens, containing boron carbide and aluminum alloy, were produced with hot pressing. Three different layers were used in the FGM samples. Then the macro and micro examinations were carried out to observe the interface between the layers, the porosity, the grain size and probable cracks in these samples. After that the specimens were solutionized at 470 °C for 1 h. Next, the artificial aging at 100 °C, 120 °C and 150 °C was applied to the FGM specimens for 96 h. During the aging treatment, the Brinell hardness measurements were made on the samples at certain intervals. Moreover, three-point bending tests were also carried out to clarify the influence of the aging treatment on the strength of the FGM. Experimental results indicated that the highest hardness values were obtained at 120 °C after the aging period of 48-65 h. The aged specimens exhibited higher bending strength than the solutionized specimens.
Keywords: kovinski materiali; metallic materials; anorganski materiali; inorganic materials; ageing; staranje; upogibni preizkus; bending test